(untitled) (Journal of Social Sciences Review, 2023)
The aim of this study is to examine the impact of honest leadership and improved infrastructure on the economic performance of the China-Pakistan Economic Corridor (CPEC) project. In this study, economic factors are taken into consideration to evaluate the economic performance of the CPEC project. For this purpose, primary data is collected from CPEC employees who are working on various projects CPEC through questionnaires. Google forms were shared with them via different social media tools such as WhatsApp, Facebook, and Instagram for the data collection. A total of 250 questionnaires were distributed, but only 220 were used for data analysis of this study. Therefore, the response rate was 88%. Hypotheses are tested in Smart-PLS version 3 by using structural equation modelling. The findings of this study revealed that there is a positive and significant impact of honest leadership and improved infrastructure on the economic performance of the CPEC project performance. In addition, improved infrastructure is found to have a more positive and significant impact due to higher beta and t-value with respect to honest leadership. The leadership of Pakistan and China should understand the importance of these variables and honest leadership for the successful completion of the CPEC project. The top management of both countries, Pakistan and China, should understand the important of these variables and honest leadership is an important factor for the successful completion of the CPEC project.